1993
DOI: 10.1111/j.1365-2915.1993.tb00674.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of tick‐borne encephalitis virus transmission by tick salivary gland extracts

Abstract: To investigate the role of ticks in TBE virus transmission, salivary gland extract (SGE) was derived from partially fed female Ixodes ricinus, Dermacentor reticulatus and Rhipicephalus appendiculatus ticks. Guinea-pigs were infested with uninfected R. appendiculatus nymphs and inoculated with a mixture of TBE virus and SGE or with virus alone. The number of ticks which on average acquired virus from feeding on animals inoculated with TBE virus and SGE from partially fed ticks was 4-fold greater than the number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
92
1

Year Published

1995
1995
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(95 citation statements)
references
References 4 publications
2
92
1
Order By: Relevance
“…Non-viraemic transmission has been demonstrated for both Thogoto virus (Orthomyxoviridae) and the flavivirus that causes tick-borne encephalitis (TBE) throughout Europe and Eurasia. Such a process only occurs when ticks are feeding close to one another and is probably enhanced by the presence of tick saliva (Labuda et al 1993). In epidemiological terms, the largest effects of non-viraemic transmission will be to provide a background force of tick infection, the scale of which depends on the proportion of infectious ticks and particularly infectious larvae the non-viraemic host produces.…”
Section: Non-viraemic Transmission Through Co-feedingmentioning
confidence: 99%
“…Non-viraemic transmission has been demonstrated for both Thogoto virus (Orthomyxoviridae) and the flavivirus that causes tick-borne encephalitis (TBE) throughout Europe and Eurasia. Such a process only occurs when ticks are feeding close to one another and is probably enhanced by the presence of tick saliva (Labuda et al 1993). In epidemiological terms, the largest effects of non-viraemic transmission will be to provide a background force of tick infection, the scale of which depends on the proportion of infectious ticks and particularly infectious larvae the non-viraemic host produces.…”
Section: Non-viraemic Transmission Through Co-feedingmentioning
confidence: 99%
“…While enhanced blood flow insures the feeding success of the arthropod, inhibiting the immune response of the host may prevent the host from becoming sensitized to the bite of the arthropod. However, there is now mounting evidence that the saliva of an arthropod vector can also enhance the infectivity of pathogens that the arthropod transmits (5)(6)(7)(8)(9)(10). Therefore, injecting arthropod-borne pathogens by syringe does not mimic natural transmission.…”
mentioning
confidence: 99%
“…Tick saliva-activated transmission of various tickborne pathogens has been demonstrated (Jones et al 1989, Labuda et al 1993, Kročová et al 2003. In the case of Borrelia spirochetes, Pechová et al (2002) reported indirect evidence for increased bacteraemia in mice injected with B. afzelii plus Ixodes ricinus SGE compared with SGE-untreated control mice.…”
Section: Discussionmentioning
confidence: 99%
“…After 5 days, engorged ticks were removed and the salivary glands were dissected and pooled. The 5-day period, for which the ticks had fed on guinea pigs, was chosen due to the best effect of SGE prepared from such ticks on the saliva-activated transmission of TBE virus (Labuda et al 1993). After washing in phosphate-buffered saline (PBS), the salivary glands were homogenized in 1 ml PBS by sonication and centrifuged at 10,000 g for 10 min.…”
Section: Methodsmentioning
confidence: 99%